Interdisziplinäre Teams in inklusiven Schulen Eine ethnografische Studie zu Fallbesprechungen in multiprofessionellen Gruppen - Labhart, David (Pädagogik, 2019)
David Labhart analyzes case reviews in multiprofessional groups in the inclusive school in the form of an ethnographic study. Using the actor-network theory, he uses the example of the canton of Zurich to show how the "interdisciplinary team" operates in practice: which tasks are worked on, how are problems located and what knowledge is integrated?